High‐Density Epicardial Activation Mapping to Optimize the Site for Video‐Thoracoscopic Left Ventricular Lead Implant. (12th May 2014) - POLASEK, ROSTISLAV; SKALSKY, IVO; WICHTERLE, DAN; MARTINCA, TOMAS; HANULIAKOVA, JANA; ROUBICEK, TOMAS; BAHNIK, JAN; JANSOVA, HELENA; PIRK, JAN; KAUTZNER, JOSEF
Optimization of Left Ventricular Lead Position Background The left ventricular (LV) lead local electrogram (EGM) delay from the beginning of the QRS complex (QLV) is considered a strong predictor of response to cardiac resynchronization therapy. We have developed a method for fast epicardial QLV mapping during video‐thoracoscopic surgery to guide LV lead placement. Methods A three‐port, video‐thoracoscopic approach was used for LV free wall epicardial mapping and lead implantation. A decapolar electrophysiological catheter was introduced through one port and systematically attached to multiple accessible LV sites. The pacing lead was targeted to the site with maximum QLV. The LV free wall activation pattern was analyzed in 16 pre‐specified anatomical segments. Results We implanted LV leads in 13 patients with LBBB or IVCD. The procedural and mapping times were 142 ± 39 minutes and 20 ± 9 minutes, respectively. A total of 15.0 ± 2.2 LV segments were mappable with variable spatial distribution of QLV‐optimum. The QLV ratio (QLV/QRSd) at the optimum segment was significantly higher (by 0.17 ± 0.08, p < 0.00001) as compared to an empirical midventricular lateral segment. The LV lead was implanted at the optimum segment in 11 patients (at an adjacent segment in 2 patients) achieving a QLV ratio of 0.82 ± 0.09 (range 0.63–0.93) and 99.5 ± 0.6% match with intraprocedural mapping. Conclusion Video‐thoracoscopic LV lead implantation can be effectively and safely guided by epicardial QLV mapping. This strategy was highly successful in targeting the selected LV segment and resulted in significantly higher QLV ratios compared to an empirical midventricular lateral segment.